An exploratory review of retirement savings investment decisions: a Malaysian perspective - Rajan, Marcia Edna Santhana; Abdullah, Amalina (Universal Publishers, 2017)
Purpose - The scanty fractions of active participation in retirement decision making is prevalent despite the Malaysian EPF's improved endeavour in aiding the private sector boost retirement income through the MIS, the performance of which are so far reaching good returns on investment. Prior literature advocates the need for more meaningful understanding of the decision making biases that influence individual retirement saving initiatives. Research to-date has reported a growing interest of the influence of psychological factors on retirement savings decisions, ranging from clear-cut to varied results, with some indistinct findings. Against this backdrop, this study attempts to provide an understanding of how psychological motivators exert an influence on retirement savings decisions. Design/methodology/approach - This study conducts a comprehensive literature review of psychological factors involving financial risk tolerance; conscientiousness; financial knowledge; and perceptions on tax matters. Findings - Results suggest the fundamental roles that financial knowledge; conscientiousness; financial risk tolerance and perceptions on tax matters play both as main effects and symbiotic influences on retirement behaviours. These biases simultaneously exert a key influence on peoples' decision to save for retirement and form interactions with other psychological factors of interest to this study in motivating retirement savings behaviours. As such a preliminary framework of psychological "pushes" and "pulls" is proposed in informing this decision. Originality/value - With the existence of limited literature on the perceptions on tax matters, this study is of value in that it highlights such an influence and its association with other factors of interest in informing the retirement investment decision.